A Ricardian analysis of the economic impacts of climate change on agricultural production in the low-income agrarian economy: Estimates from Malawi's 2010–2019 LSMS longitudinal data - Mulagha Maganga, Assa; Chiwaula, Levison S; Kambewa, Patrick; Ngaiwi, Mary Eyeniyeh (Elsevier, 2024)
Quantifying the economic impacts of extreme climate scenarios on agriculture at a country level is important, informing the formulation of tailored adaptation policies and sustainable livelihoods. This study examined the current and potential economic impacts of climate change on Malawi's agriculture using Ricardian analysis based on a four-year World Bank's Living Standards Measurement Survey (LSMS) panel data from 1,246 farming households. The marginal impact analysis was conducted for temperature and rainfall. The study then predicted the impact of climate scenarios on net revenue up to the year 2099. The results revealed that more warming will negatively affect agriculture returns on the one hand, while more precipitation will generate gains on the other hand. An ensemble of Global Circulation Models' simulation affirms that impacts from global warming will be more important than those from precipitation change. The impacts are non-neutral to production efficiency with technically efficient farmers having moderate impacts in magnitude relative to inefficient farmers. With strategic climate adaptation choices, results show the potential to abate some of the damages and enhance positive gains from future climate change.